150-million-year-old sea spiders (Pycnogonida: Pantopoda) of Solnhofen. (17th November 2019) - Sabroux, Romain; Audo, Denis; Charbonnier, Sylvain; Corbari, Laure; Hassanin, Alexandre
Abstract : Sea spiders (Pycnogonida) are strange arthropods characterized by a unique morphology, including reduced body, egg-carrying appendages and a proboscis. This peculiar body plan dates at least as early as the first undoubted occurrence of the group, 425 million years ago in the Silurian. All extant species belong to the order Pantopoda, characterized by cylindrical legs and an unsegmented abdomen. Palaeozoic fossils are much more diversified and exhibit features very different from pantopod morphology such as a segmented abdomen, limbs specialized to swim, or even a flagellum. The few Mesozoic fossils from the single Jurassic palaeoenvironment of La Voulte-sur-Rhône (south-eastern France) instead have strong affinities to Pantopoda. Here, we investigate the morphology of nine sea spider fossils using a new photographic protocol to document morphology, combining focus stacking and differential colourization. We also describe two new species of fossil pycnogonids from the Late Jurassic of Solnhofen (southern Germany): Colossopantopodus nanus sp. nov. is closely allied to a large species from La Voulte-sur-Rhône, but distinct in its smaller size; the other, ? Eurycyde golem sp. nov., is the first known fossil representative of the extant family Ascorhynchidae. Seven additional specimens, too poorly preserved for taxonomic description, are illustrated. The comparisons reveal that the shallow lagoons of Solnhofen contained a diverse assemblage of pantopods. Altogether with the fauna of La Voulte-sur-Rhône, the results suggest that Pantopoda became the dominant pycnogonid taxon of both deep and shallow marine waters after the Jurassic. http://zoobank.org/urn:lsid:zoobank.org:pub:3C7AB6BF-A161-435F-B85C-53220A833188